2015
DOI: 10.1159/000440818
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Neutrophil-to-Lymphocyte Ratio as a Severity Predictor of Acute Appendicitis, Length of Hospital Stay and Postoperative Complication Rates

Abstract: Background: Numerous screening tools have been reported to aid in diagnosing appendicitis, but have poor severity prediction and lack accurate estimation of postoperative complications or total length of hospital stay (LOS). Aim: This study aims at evaluating the utility of neutrophil-to-lymphocyte (NLR) ratio in predicting the severity of appendicitis, LOS and 30-day complication rates. Methods: Patients who underwent appendicectomy over a 4-year period were evaluated. Demographics, blood results, severity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
3
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 22 publications
(36 reference statements)
1
24
3
11
Order By: Relevance
“…According to their data, NLR was a good indicator to predict severity of appendicitis and estimate the length of the stay time; cutoff value was higher in the pediatric population (7.53, sensitivity: 80%, specificity: 55%) compared with that of the adults (6.35, sensitivity: 85%, specificity: 48%) (19). The current study did not evaluate the severity of appendicitis, but there was no difference in the length of stay between the AA and NA groups.…”
Section: Discussionmentioning
confidence: 99%
“…According to their data, NLR was a good indicator to predict severity of appendicitis and estimate the length of the stay time; cutoff value was higher in the pediatric population (7.53, sensitivity: 80%, specificity: 55%) compared with that of the adults (6.35, sensitivity: 85%, specificity: 48%) (19). The current study did not evaluate the severity of appendicitis, but there was no difference in the length of stay between the AA and NA groups.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of 663 patients with acute appendicitis from our institution demonstrated that an NLR value of >6.35 was associated with severe acute appendicitis and a prolonged hospital stay [10] . Similarly, Beecher et al [16] demonstrated that an NLR >5.47 was more accurate than CRP and WBC at detecting complicated acute appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil to lymphocyte ratio (NLR) is a relatively novel biomarker that has been studied in the setting of surgical oncology, acute appendicitis and acute pancreatitis among other conditions [9][10][11] . The principle behind NLR is that neutrophil levels rise as part of the inflammatory cascade, whereas lymphocytes are depleted during sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…The white blood cell (WBC), CRP, and total bilirubin values, the neutrophil-to-lymphocyte ratio, and the combination of radiology and laboratory scoring systems are used for severity evaluation. [8][9][10][11][12] The AS and the AIRS were designed to help diagnose AA. The aim of this study was to retrospectively assess use of the AS and the AIRS to evaluate severity of appendicitis.…”
Section: Introductionmentioning
confidence: 99%